Effect of Lactobacillus acidophilus supernatants on body weight and leptin expression in rats - Lewis Stephen J; Zhang Jian; Halper Jaroslava; Sousa Renato; Li Wan-I O (BMC, 2008)
Abstract Background Lactobacillus extracts and supernatants have been used as probiotics in human and veterinary medicine for their ability to enhance wound healing and immunity. Previous data from our laboratory demonstrated that Lactobacillus supernatant (LS) stimulated wound healing, angiogenesis and proliferation of embryonic cells after topical application. This current study shows that LS after its administration into the cerebral ventricles of male rats exerts systemic effects. Methods The right lateral cerebral ventricle of young male rats was accessed through intracerebroventricular cannulation (ICV) under anesthesia and aseptic conditions. One group of control rats received saline solution, a second control group received 0.8 M lactic acid solution (to control for acidity of LS), and a third group received LS. The animals were sacrificed 12, 24, 48, 96 and 120 hours after the injection. Selected tissues were collected, fixed in 10% buffered formalin and used for immunohistochemistry and in situ hybridization. Other tissues were frozen and extracted for immunoblotting Results LS-injected animals had a slight decrease in body weight when compared to their initial weight and to both control groups. Using immunohistochemistry and in situ hybridization leptin expression was studied in multiple brain sections and peripheral adipose tissue of control and LS-injected rats. Strong cytoplasmic stain was observed by both techniques in neurons of the cerebral cortex, thalamus, hypothalamus, hippocampus and, to lesser degree, in the cells of the choroid plexus in the LS-injected rats. Control animals demonstrated much less intense staining in neurons located in the same regions using immunohistochemistry and almost no staining with in situ hybridization technique. Adipose tissue exhibited slight presence of leptin in LS-treated animals. In contrast no immunohistochemical staining for GM-CSF and TNFα was observed in brains from control and treated rats. Western blotting showed mild increase in leptin and leptin receptors in intestines and retroperitoneal adipose tissues of LS-injected rats. Conclusion This study demonstrates that direct administration of LS into rat CNS leads to a decrease in body weight of rats and an increase in the expression of leptin in specific areas of the brain and retroperitoneal adipose tissue.